AN INTEGRATED EXISTENTIAL FRAMEWORK FOR TRAUMA THEORY - Wilmshurst, Kaitlin (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2020)
In this paper, an integrated existential framework for trauma theory is presented. The framework is based on the clustering of current trauma theories into physical, relational, and intrapersonal categories, and the relation of these three clusters to Irvine Yalom’s ultimate existential concerns of life/death, connection/isolation, and freedom/responsibility. Recent research has revealed an interplay between the physiological and psychosocial aspects of traumatic experiences, suggesting that a theoretical integration which includes consideration of physiological change, fear conditioning, and relational impacts is required to fully address the impacts of trauma. The fourth existential concern, meaning/meaninglessness, is argued to underlie all of the aspects of trauma, forming a common connection between all theories. This paper undertakes a brief review of current theories in traumatology to illustrate the validity of the three theoretical clusters, explores the current application of existential theory to the conceptualization of trauma, and presents a unifying organizational framework for trauma theory based in existentialism. Critiques of theory integration and existentialism are explored, followed by an analysis of risks for existential theory in the application of this framework. Implications for future research and social work practice based on the existential framework are also presented.